1992
DOI: 10.1152/jn.1992.68.5.1558
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory discharge in the visual system: does it have a functional role?

Abstract: 1. The discharge of individual neurons in the visual cortex and lateral geniculate nucleus (LGN) of anesthetized and paralyzed cats and kittens was examined for the presence of oscillatory activity. Neural firing was evoked through the monoptic or dichoptic presentation of drifting gratings and random sequences of flashed bars. The degree to which different oscillatory frequencies were present in neural discharge was quantified by computation of the power spectra of impulse train responses. 2. Action potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
164
5

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(183 citation statements)
references
References 56 publications
14
164
5
Order By: Relevance
“…Such stimulus locking of oscillatory responses in the retina and the LGN has been described in a number of studies (Ariel et al 1983;Ghose & Freeman 1992;Wö rgö tter & Funke 1995). However, the epoch of stimulus-locked synchronization is of short duration and replaced by a sustained phase of synchronous oscillatory ring that is no longer time locked to stimulus onset and hence needs to Phil.…”
Section: Retinal Origin Of Response Synchronizationmentioning
confidence: 63%
“…Such stimulus locking of oscillatory responses in the retina and the LGN has been described in a number of studies (Ariel et al 1983;Ghose & Freeman 1992;Wö rgö tter & Funke 1995). However, the epoch of stimulus-locked synchronization is of short duration and replaced by a sustained phase of synchronous oscillatory ring that is no longer time locked to stimulus onset and hence needs to Phil.…”
Section: Retinal Origin Of Response Synchronizationmentioning
confidence: 63%
“…Ghose and Freeman (1992) observed that a large percentage of LGN cells showed gamma-band oscillations ~ 50 Hz that were actually stronger than responses in cortical cells.…”
Section: Thalamus and Network Oscillationsmentioning
confidence: 95%
“…However, most studies investigating synchrony between single V1 cortical neurons have focused either on the effect of altering the "gestalt" characteristics of the stimulus (Livingstone, 1996) or have used indirect measurements such as the synchrony of multiunit activity (MUA) (Lamme and Spekreijse, 1998) or the strength of oscillations in single-unit activity, MUA, or the local field potential (LFP) (Gray et al, 1989; synchrony, this is because different stimuli might recruit different subpopulations of neurons in the recorded signal. For measures of oscillatory firing, this is because the stimulus dependence of oscillations is controversial (Ghose and Freeman, 1992;Young et al, 1992) and because some studies have failed to find a strong relationship between oscillatory firing and synchronous firing of single neurons (Samonds and Bonds, 2004) (but see Maldonado et al, 2000). To compare the sensitivity of spike count and spike timing correlation between single V1 neurons, we therefore investigated the orientation dependence of synchrony in our population of pairs.…”
Section: Orientation Dependence Of Spike Timing Correlationmentioning
confidence: 99%